PENGARUH ALOKASI DANA DESA (ADD) TERHADAP PEMBANGUNAN, PEMBERDAYAAN MASYARAKAT DESA SE-KECAMATAN MABA TENGAH (Studi Empiris pada Pemerintah Kabupaten Halmahera Timur Kecamatan Maba Tengah) - Manoma, Suharli (Jurnal MS, 2023)
National and regional development is an inseparable part of village development activities, since the concentration of the population is still dominant in the village, so that the village is a base of socioeconomic and Â political power that needs serious attention from the goverment. In order to determine the effect of allocation village of rural development and community empowerment village in the District Middle Maba District East Halmahera. The location of the research author in 12 village located in the region District Middle Maba District East Halmahera. Responden this research is a village society scattered in 12 village in the District Middle Maba. Sample a total of 127 people. Sampling technique in purposive sampling. This study using data analysis multiple linier regression. Analysisi using the regression test obtained value significantly by 0,000 or smaller than the value of probability (p-value) 0,05 (0,000 < 0,05) this means that variable allocation village has a significant effect together (simultaneous) to the rural development and community empowerment village in the district Middle Maba District East Halmahera. Therefore, there are significant influence of the allocation village of rural development and community empowerment village in the District Middle Maba District East Halmahera.Â Â